2009
DOI: 10.1021/ja808573f
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Biliverdin Radical Intermediate in Phycocyanobilin:Ferredoxin Oxidoreductase Identified by High-Field EPR and DFT

Abstract: The cyanobacterial enzyme phycocyanobilin:ferredoxin oxidoreductase (PcyA) catalyzes the twostep four-electron reduction of biliverdin IXα to phycocyanobilin, the precursor of biliprotein chromophores found in phycobilisomes. It is known that catalysis proceeds via paramagnetic radical intermediates, but the structure of these intermediates and the transfer pathways for the four protons involved are not known. In this study, high-field electron paramagnetic resonance (EPR) spectroscopy of frozen solutions and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
53
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 69 publications
3
53
0
Order By: Relevance
“…In the substrate-free PcyA structure, the pro- BV [13]. Substitution of either residue with a non-proton-donating 89 amino acid prevents transfer of a second electron thereby stabiliz-90 ing the one-electron reduced BVHÅ radical [16]. In addition to D-91 ring exovinyl group reduction, His88 also plays a critical role in 92 A-ring endovinyl reduction since the H88Q variant is unable to re-93 duce the A-ring vinyl group of exogenous DHBV [12].…”
mentioning
confidence: 99%
“…In the substrate-free PcyA structure, the pro- BV [13]. Substitution of either residue with a non-proton-donating 89 amino acid prevents transfer of a second electron thereby stabiliz-90 ing the one-electron reduced BVHÅ radical [16]. In addition to D-91 ring exovinyl group reduction, His88 also plays a critical role in 92 A-ring endovinyl reduction since the H88Q variant is unable to re-93 duce the A-ring vinyl group of exogenous DHBV [12].…”
mentioning
confidence: 99%
“…1B) (17, 18). More recent EPR spectroscopy and density-functional theory computations on the D105N mutant of PcyA revealed potential protonation states of the semireduced BV radical intermediate (25), which, in turn, indirectly implicated the role of proton donors within the active site.…”
mentioning
confidence: 99%
“…These computations were performed on the BV, Glu76, His88 and Asp105 system (structure extracted from the D105N diffraction data) in gas phase. In that model system, all heteroatoms were frozen and the propionate groups were replaced by methyl groups [7]. The new intermediate proposed in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…The new intermediate proposed in Ref. [7] presents the C-OH of the A-ring oriented towards His88 while the C-OH of the D-ring is directed to the oxygen atom of the A-ring. In 2010, the group of Higawara suggested that Glu76 is playing a role in the proton donation process while His88 would be important for the second reduction step, in agreement with the previous works [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation